Effect of strong magnetic field on surface polaritons in ZnO - Venger, E.F.; Ievtushenko, A.I.; Melnichuk, L.Yu.; Melnichuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Using the attenuated total reflectance technique, we studied the effect of strong
uniform magnetic field H on the main properties of surface polaritons in ZnO single
crystals. The used orientations were C || y , k ⊥ C , xy || C , H ⊥k , H || y , k x =k ,
ky,z =0; the free charge carrier concentration varied from 9.3×10¹⁶ up to 2.0 × 10¹⁸ cm⁻³. It has been shown that three dispersion curves exist in the zinc oxide
single crystals for the above orientation. The possibility of excitation of an additional
dispersion branch in optically anisotropic semiconductors placed into magnetic field is
found using ZnO single crystals as an example. The damping coefficients for surface
phonon and plasmon-phonon polaritons have been determined.